Kajian Interior PAUD dan Taman Bacaan Masyarakat di Ruang Multifungsi di Area-Eks Lokalisasi Dolly Surabaya - Olivia Renata Kuswandi; Mariana Wibowo (Intra, 2019)
Early childhood education (PAUD) is an education level that plays an important role in the formation of an individual because the child is in his golden age. For this reason, it is necessary to do a study with the aim of future development. The majority of early childhood classrooms joins other facilities so that teachers do not have the space to freely develop creativity and learning ideas for the development of the child. This is the background of the research on the evaluation of early chilhood education and reading corner’s interior design in a limited area with the object of research located in the area of Dolly's ex-localization in Surabaya. The research location was chosen because researcher want to develop space quality of early childhood education and community’s reading corner in that area . The research method used is a qualitative method with a case study approach. The chosen research subjects were early childhood and visitors to community’s reading corner in the area. The aspects studied were things related to the object and subject, namely the interior design of early chilhood education and reading corner in a limited space. The result of this study are the implementation of how to make a limited space as optimal as possible to stimultae the development of early childhood education and facilitate actitivities in community’s reading corner.